SIKAP TERHADAP VAKSIN COVID-19 TERHADAP VAKSINASI COVID-19 PADA SISWA SMP-SMA - Josia, Michael; Fadilah, Tubagus Ferdi (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUND Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the newly discovered Coronavirus, namely the SARS-CoV-2 virus. Daily cases of COVID-19 increased rapidly by up to 500% from May 15 to Jun 17, 2021, especially in Banten province; there were 53,472 cases, of which 10.4% were cases of children aged 6-18 years, causing an emergency to prevent the spread of COVID-19. One of the efforts to prevent COVID-19 in children can be through vaccination. Therefore, this study assessed students' attitudes towards the COVID-19 vaccine, evaluated data on COVID-19 vaccinations in students, and assessed the relationship between student attitudes towards the COVID-19 vaccine and COVID-19 vaccination in students. METHODS This study used a cross-sectional design with a population of students from Santa Patricia Junior High School with a sample size of 90 participants using cluster sampling technique and simple random sampling and then analyzed using the exact-fisher test. RESULTSThe results of the study prove that the most prominent characteristic aspects are female gender (64.4%), Age below or equal to 15 years (57.8%), having received the COVID-19 vaccine (86.7%), having a positive attitude towards the COVID-19 vaccine (85.5%), was influenced by other people around him (97.8%) and wanted to vaccinate against COVID-19 (86.7%). Students' attitudes towards the COVID-19 vaccine with COVID-19 vaccination had p=0.324. CONCLUSION The analysis did not show a significant relationship between students' attitudes towards the COVID-19 vaccine and the coverage of the COVID-19 vaccination (p=0.324; p>0.05). KEYWORDS: COVID-19 Vaccine, COVID-19 Vaccination, Junior High School, High School, COVID-19 Pandemic, Theory of Planned Behavior